2015
DOI: 10.1038/ncomms7194
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B cell receptor binding to galectin-1 modifies galectin-1/carbohydrate affinity to modulate specific galectin-1/glycan lattice interactions

Abstract: Galectins are glycan-binding proteins involved in various biological processes including cell/cell interactions. During B-cell development, bone marrow stromal cells secreting galectin-1 (GAL1) constitute a specific niche for pre-BII cells. Besides binding glycans, GAL1 is also a pre-B cell receptor (pre-BCR) ligand that induces receptor clustering, the first checkpoint of B-cell differentiation. The GAL1/pre-BCR interaction is the first example of a GAL1/unglycosylated protein interaction in the extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 53 publications
2
42
0
2
Order By: Relevance
“…2D and movie S3), which is best explained by the formation of complex aggregates containing pre-BCR, galectin-1, and other cell surface glycoproteins. To provide evidence that the marked slowdown of the pre-BCR bound to galectin-1 could be attributed in part to carbohydrate-mediated lattices with other glycoproteins (37), we also performed experiments in the presence of excess lactose (10 mM) to block the lectin-binding site of galectin-1 (fig. S6B).…”
Section: Resultsmentioning
confidence: 99%
“…2D and movie S3), which is best explained by the formation of complex aggregates containing pre-BCR, galectin-1, and other cell surface glycoproteins. To provide evidence that the marked slowdown of the pre-BCR bound to galectin-1 could be attributed in part to carbohydrate-mediated lattices with other glycoproteins (37), we also performed experiments in the presence of excess lactose (10 mM) to block the lectin-binding site of galectin-1 (fig. S6B).…”
Section: Resultsmentioning
confidence: 99%
“…Gal-1 recognizes multiple galactose-b1-4-N-acetyl-glucosamine (N-acetyl-lactosamine [LacNAc]) units present on the branches of N-or O-linked glycans on diverse cell surface receptors, including CD45, CD43, CD69, pre-BCR, and vascular endothelial growth factor R2 (11,(19)(20)(21). Different glycosyltransferases act in concert to create Gal-1-specific ligands, including N-acetylglucosaminyltransferase 5 (MGAT5), an enzyme that generates b1,6-N-acetylglucosamine-branched complex N-glycans and the core-2 b1-6-N-acetylglucosaminyltransferase 1 (C2GNT1), an enzyme that catalyzes branching of core-2 O-glycans.…”
Section: Gal-1: a Sweet Checkpoint In The Resolution Of Inflammatorymentioning
confidence: 99%
“…Following antigen challenge, Gal-3 deficiency led to enhanced plasma cell differentiation and unleashed immunoglobulin production, both in B1 and B2 cells [87,88]. Finally, elegant studies reported that, during B-cell development, Gal-1 secreted by bone marrow stromal cells acts as a pre-B cell receptor ligand to modulate B cell maturation through mechanisms involving displacement of Gal-1/glycan lattices and shift toward a glycosylation-independent Gal-1-mediated protein-protein interaction [89]. Thus, although not investigated in such detail as the T cell compartment, these studies suggest that galectins may play different regulatory roles during the lifespan of B cells, targeting their maturation, differentiation, signaling, tolerance and survival.…”
Section: Regulatory B Cellsmentioning
confidence: 99%